1989
DOI: 10.1152/ajpgi.1989.257.6.g917
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of agonist-activated calcium influx by extracellular pH in rat pancreatic acini

Abstract: The biochemical and Ca2+ transport pathways involved in generating the hormone-evoked Ca2+ signal are reported to be influenced by pH. The present study was designed to determine the effect of extracellular pH (pHo) and intracellular pH (pHi) on hormone-stimulated Ca2+ transport. We used rat pancreatic acini and measured free cytosolic Ca2+ concentration ([Ca2+]i) with fura-2, pHi with 2,7-bis(carboxyethyl)-5(6)-carboxyfluorescein (BCECF), and Ca2+ fluxes with 45Ca2+. In the presence of external Ca2+, increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 0 publications
7
19
1
Order By: Relevance
“…This inhibition is probably mediated through a direct effect of external H+ on th e apical Ca2+ influx pathway, which is supported by our previous findings th a t both apical and basolateral acidification lead to comparable decreases in intracellular pH, but only low apical pH inhibits transcellular Ca2+ transport [7]. In various cell types, including other epithelial tissues, a similar pH dependence of Ca2+ entry pathways has been described [31,32], In addition, extracellular H+ are know n to inhibit voltage-gated Ca2+ channels in excitable tissues by changing their conformation and m odifying their gating properties [33], The molecular n atu re of the epithelial Ca2+ influx pathway involved in Ca2+ reabsorption in the distal nephron has rem ained obscure so far. Several types of voltage-dependent Ca2+ channels have been described in renal distal tu b u lar cells of different species.…”
Section: Discussionsupporting
confidence: 82%
“…This inhibition is probably mediated through a direct effect of external H+ on th e apical Ca2+ influx pathway, which is supported by our previous findings th a t both apical and basolateral acidification lead to comparable decreases in intracellular pH, but only low apical pH inhibits transcellular Ca2+ transport [7]. In various cell types, including other epithelial tissues, a similar pH dependence of Ca2+ entry pathways has been described [31,32], In addition, extracellular H+ are know n to inhibit voltage-gated Ca2+ channels in excitable tissues by changing their conformation and m odifying their gating properties [33], The molecular n atu re of the epithelial Ca2+ influx pathway involved in Ca2+ reabsorption in the distal nephron has rem ained obscure so far. Several types of voltage-dependent Ca2+ channels have been described in renal distal tu b u lar cells of different species.…”
Section: Discussionsupporting
confidence: 82%
“…Slight acidification and alkalinization of external solutions results in reduction and elevation of SOC influx, respectively. Previous work performed on pancreatic acini (Muallem et al, 1989) and the epithelial colon carcinoma cell line HT 29 (Nitschke et al, 1996) have demonstrated sensitivity of Ca 2ϩ entry to acidic pH.…”
Section: Discussionmentioning
confidence: 97%
“…Since the ionization states of amino acid residues are highly dependent on pH, it is possible that acidification may result in the inactivation of second messenger mediators of SOC. In this regard, attenuation of SOC in pancreatic acinar cells by acidification is relatively independent of intracellular pH when extracellular pH is held constant, suggesting that added protons act to modulate SOC through the modification of cellular structures on the external surface of the cell membrane (Muallem et al, 1989). An alternative explanation for the reduction of SOC by extracellular acidification is the alteration of Na ϩ /H ϩ exchanger operation through either intra-or extracellular acidification (Siesjö et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…To preclude these possibilities, we examined the effect of reducing extracellular pH on the Ca 2ϩ entry activated by thapsigargin and by arachidonic acid. Modest reductions in extracellular pH have been shown to have a profound inhibitory effect on capacitative Ca 2ϩ entry in a range of different cell types (23)(24)(25)(26), and in the case of the storeoperated channel I CRAC , this has been shown to reflect a direct action of extracellular protons on the channel (27). 2 As shown in Fig.…”
Section: Arachidonate-mediated Ca 2ϩ Entry In Hek293 Cellsmentioning
confidence: 99%